Pendidikan Moral dan Sosial Anak dalam Islam: Studi Hadis tentang Interaksi Nabi SAW - Muhammad Ruslan; Abd Rahman; Suraiya Chapakiya (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Moral and social education in Islam plays a crucial role in shaping children's character, developing noble character and social responsibility. In this context, the Prophet Muhammad (peace be upon him) serves as a prime role model, whose behavior and sayings provide comprehensive guidance for the development of character values. This study aims to analyze authentic hadiths depicting the Prophet's interactions with children to uncover key moral and social values that can be integrated into contemporary Islamic education. The method used is a descriptive qualitative approach with thematic analysis techniques. Data were collected from relevant authentic hadith literature and then analyzed to identify moral values such as honesty, compassion, justice, empathy, and respect for children's rights. The analysis also considered the historical and social context of the hadiths, allowing interpretations of the values to be tailored to current educational needs. The results show that the Prophet Muhammad taught moral and social principles not only through verbal statements but also through concrete examples in his daily life. For example, he demonstrated gentleness toward children, respected their opinions, appreciated good behavior, and reprimanded them wisely when mistakes occurred. This approach creates an educational pattern that is not authoritarian, but rather builds positive emotional bonds between educators and students. These findings emphasize the relevance of prophetic values in shaping character education in the modern era, which often faces challenges of morality and the degradation of social values. Integrating these values into the curriculum and educational practices in schools and families is expected to produce individuals who are not only intellectually intelligent but also possess high moral integrity and social sensitivity.